2010
DOI: 10.1080/08897070903442459
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Substance Abuse Treatment Entry among Rural Illicit Stimulant Users in Ohio, Arkansas, and Kentucky

Abstract: Illicit drug use in the rural United States is increasingly common, yet little is known about drug users’ treatment-seeking behaviors. This study identifies predictors of substance abuse treatment entry over 24 months among 710 illicit stimulant users in rural areas of Ohio, Arkansas, and Kentucky. Active users of powdered cocaine, crack cocaine, and/or methamphetamine (MA) were recruited using respondent-driven sampling. Participants completed structured interviews at baseline and follow-up questionnaires eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 23 publications
(53 reference statements)
4
50
0
6
Order By: Relevance
“…Subsequent analysis will explore potential predictors of the trajectories. Overall, we know much more regarding use of substance use services by substance users(1-2) than about mental health service use by substance users.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent analysis will explore potential predictors of the trajectories. Overall, we know much more regarding use of substance use services by substance users(1-2) than about mental health service use by substance users.…”
Section: Discussionmentioning
confidence: 99%
“…(9) Prior research with this sample found no association between age, race, gender, and treatment entry for substance use. (1)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No Brasil, não existem modelos de tratamento criados especificamente para essa demanda. Entre usuários de substâncias psicoativas em geral, usuários de crack são descritos como os que menos procuram ajuda 11 . Por isso e pela demora em buscar tratamento, a maioria dos pacientes já se apresenta aos serviços com muitos prejuízos, preferindo tratamentos em locais com internação e tendendo a ter baixa adesão ambulatorial após a internação 12 .…”
Section: Introductionunclassified